Towards Implementing a New Maritime Accident Reporting and Analysis System in Namibia - Amweelo, Moses (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2018)
When Namibia became an independent state in 1990, the Republic of Namibia inherited the Merchant Shipping Act No. 57 of 1951 from the old South Africa regime. The Merchant Shipping Amendment Act, 1991 was signed into force “in order to adjust its provisions in view of the independence of Namibia; and to provide for incidental matters.” Maritime issues were placed under the authority of the Ministry of Works and Transport, however, without any particular defined body, except Department of Transport, to enforce the provisions of the amendment Act (The Merchant Shipping Act No. 57 of 1951, as amended in 1991). In 1995 the Directorate Maritime Affairs was established to be the Ministry’s executing body, and one of the first tasks taken on in order to get a firm picture of the maritime legal situation was to carry out an analyse of the Merchant Shipping Act. According to Professor Hilton Staniland of the University of Natal, in his executive summary he states among others: ‘’The 1951 Act is out of date and places, in particular, the safety of life and ships at sea, the protection of the marine environment provide Namibia a disadvantageous position as far as international maritime transport and trade is concerned. It is interesting in this connection to note the concerns at that time expressed by representatives from the fishing industry: ‘’The industry therefore (not sufficient Namibians with certificates) favours the amendment of section 83 of the Merchant Shipping Act 1951 in order to provide for the more ready recognition of foreign certificates. Section 83 of the Act opens up for allowing holders of foreign certificates to serve on board Namibian ships. In the meantime the newly established Directorate Maritime Affairs should make a choice: Either hastily accede to the International Maritime Organisation (IMO) Conventions or first ensure that relevant instruments were in place and then work for the accession to the Conventions. It was decided to ensure that the Directorate would be able to enforce the Conventions and then accede. The aims of the directorate are: to ensure the safety of life and property at sea; to prevent and combat pollution of the marine environment by ships and to promote the maritime interests of Namibia.